Kritik Sosial dalam Puisi Negeri di Tepi Jurang Karya Fadli Zon dan Ayyuha al-Nas Karya Tamim Barghouti - Al-amien, Habib (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2024)
This research focused on the patterns of social criticism found in the poems of Fadli Zon and Tamim, both of whom are political experts, through a comparison of their similarities and differences. The method used in this research is descriptive qualitative research. The data collection method employed is the reading and note-taking method. The data sources are Fadli Zon's poem titled "Negeri di Ujung Jurang" and Tamim Barghouti's poem titled "Ayyuha al-Nas." The results of this research showed that the social criticism in the poems of Fadli Zon and Tamim each have their own distinctive characteristics. Different political perspectives are also evident in these poems through the issues raised. However, both Fadli Zon and Tamim obscured the countries they refer to, albeit for different purposes. Fadli Zon obscured the country he criticizes, while Tamim obscured the country he defends.Keywords – Critic, Fadli Zon, Poem, Politic, Tamim.